The Identification of Electrolyte Property of Humus-Contained Andosol Soil Using Cu-Zn Electrodes - Irvan Maulana Firdaus; Diva N.M.D. Masyitoh; Tharra A.N. Azizah; Febiyanto Febiyanto (Walisongo Journal of Chemistry, 2020)
This study investigated the electrolyte property of humus-contained andosol soil using Volta cell. The electrodes that are used were Cu and Zn for cathode and anode, respectively. This research was done by varying electrode area and distance between Cu and Zn electrodes. The varied electrode area was 20, 30, and 40 cm2, whereas the electrode distance was 3, 4, and 5 cm. Then, the current and voltage profiles of Volta cell system were measured using a digital multimeter. The result showed that humus-contained andosol soil has an electrolyte property. Electrolyte property of andosol soil might be due to the humus substance that has a high cationic-exchange capacity. Besides, it showed that the increase of the electrode area, the current and voltage were increased gradually. In contrast, the increase in current and voltage could be found by the decrease of electrode distance. In addition, the use of 24-Volta cells system enhancing current and voltage compared to a single cell. It suggests that the increase of current and voltage was relatively proportional to the number of Volta cell. Therefore, this research can be a reference for the identification of electrolyte property of natural or waste materials.